Altered intrinsic regional brain activity in male patients with severe obstructive sleep apnea: a resting-state functional magnetic resonance imaging study - Peng DC (Dove Medical Press, 2014)
De-Chang Peng,1 Xi-Jian Dai,1,2 Hong-Han Gong,1 Hai-Jun Li,1 Xiao Nie,1 Wei Zhang3 1Department of Radiology, The First Affiliated Hospital of Nanchang University, Jiangxi, 2Department of Imaging and Interventional Radiology, Prince of Wales Hospital, The Chinese University of Hong Kong, Shatin, Hong Kong, Special Administrative Region, 3Department of Pneumology, The First Affiliated Hospital of Nanchang University, Jiangxi, People’s Republic of China Background: Previous studies have demonstrated that obstructive sleep apnea (OSA) is associated with abnormal brain structural deficits. However, little is known about the changes in local synchronization of spontaneous activity in patients with OSA. The primary aim of the present study was to investigate spontaneous brain activity in patients with OSA compared with good sleepers (GSs) using regional homogeneity (ReHo) analysis based on resting-state functional magnetic resonance imaging (MRI). Methods: Twenty-five untreated male patients with severe OSA and 25 male GSs matched for age and years of education were included in this study. The ReHo method was calculated to assess the strength of local signal synchrony and was compared between the two groups. The observed mean ReHo values were entered into Statistical Package for the Social Sciences software to assess their correlation with behavioral performance. Results: Compared with GSs, patients with OSA showed significantly lower ReHo in the right medial frontal gyrus (BA11), right superior frontal gyrus (BA10), right cluster of the precuneus and angular gyrus (BA39), and left superior parietal lobule (BA7), and higher ReHo in the right posterior lobe of the cerebellum, right cingulate gyrus (BA23), and bilateral cluster covering the lentiform nucleus, putamen, and insula (BA13). The lower mean ReHo value in the right cluster of the precuneus and angular gyrus had a significant negative correlation with sleep time (r=-0.430, P=0.032), and higher ReHo in the right posterior lobe of the cerebellum showed a significant positive correlation with stage 3 sleep (r=0.458, P=0.021) and in the right cingulate gyrus showed a significant positive correlation with percent rapid eye movement sleep (r=0.405, P=0.045). Conclusion: Patients with OSA showed significant regional spontaneous activity deficits in default mode network areas. The ReHo method is a useful noninvasive imaging tool for detection of early changes in cerebral ReHo in patients with OSA. Keywords: obstructive sleep apnea, regional homogeneity, intermittent hypoxia, functional magnetic resonance imaging, resting state, spontaneous activity